Accountability: a necessity to pro-poor service delivery in Municipal Councils in Uganda - David Mwesigwa; Ibrahim Abiodun Oladapo (Goodwood Publishing, 2021)
Purpose: There is mounting fear that the present-day Local Government managers do not appropriately respond to pro-poor service delivery. Yet, the number of people lacking access to quality services is swelling. This fault has placed a growing burden on Local Governments to enhance local councilors' political accountability by ensuring that the basic services are made delivered to citizens with accountability. Given the different challenges and observed shortage of political accountability in Uganda, this study examined the contribution of political accountability towards achieving pro-poor service delivery in a Ugandan Municipality. Research methodology: Using five Focus group discussions, perspectives on accountability are debated as a foundation for improving service delivery. Limitation: The study covers only Uganda and may not easily be generalised to other countries. Results: Results indicate that political accountability is key to implementing a municipal development plan. Contribution: The study contributes to knowledge so that hands-on accountability holds potential and requires more consideration as a means to assimilate learning-based methods and role-players network to back up the delivery of pro-poor services. It is proposed that local councilors become more responsive to meet the growing need for pro-poor service delivery in a Municipal council. Keywords: Accountability, Pro-poor service delivery, Horizontal, Vertical, Diagonal